REPRODUCTIVE BIOLOGY OF Thynnichthys thynnoides Bleeker, 1852 FROM IN THE PINANG LUAR OXBOW LAKE BULUHCINA VILLAGE, SIAK HULU DISTRICT, KAMPAR REGENCY, RIAU PROVINCE - Sally Rizky; Ridwan Manda Putra; Deni Efizon (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Thynnichthys thynnoides (Cyprinidae) is a type of freshwater fish that inhabits the Pinang Luar Oxbow Lake. This fish has high economical value, around Rp. 25,000–35,000 /kg. This study aims to understand the reproductive biology of Thynnichthys thynnoides from the lake had been conducted during rainy season from March–April 2016. There were 169 fishes (75.04–199.32 mm TL, 3.78–73.01 gr BW, and 0.01–6.22 gr GW) were collected and measured. There were 145 male and 24 female captured. Sex ratio of males and females was 6:1. In each sampling, there were males in the 1st-5th maturity level, while that of the females were in the 1st-4th maturity level. The gonad somatic index was 0.14–14.90%. fecundity is around 26,250–33,894 eggs/fish, and the egg diameter was 0.33–0.39 mm. This structure indicate that the Thynnichthys thynnoides was a total spawner and they may spawn throughout the rainy season.Keywords : Thynnichthys thynnoides, rainy season, sex ratio, maturity level, gonad somatic index